Safety of single-dose bedaquiline combined with rifampicin for leprosy post-exposure prophylaxis: A Phase 2 randomized non-inferiority trial in the Comoros Islands - de Jong, Bouke Catherine; Nourdine, Said; Bergeman, Auke Thomas; Salim, Zahara; Grillone, Silahi Halifa; Braet, Sofie Marijke; Wirdane Abdou, Mohamed; Snijders, Rian; Ronse, Maya; Hoof, Carolien; Tsoumanis, Achilleas; Ortuño-Gutiérrez, Nimer; et al. (PLoS medicine, 2024)
To reduce leprosy risk in contacts of patients with leprosy by around 50%, the World Health Organization (WHO) recommends leprosy post-exposure prophylaxis (PEP) using single-dose rifampicin (SDR). Results from a cluster randomized trial in the Comoros and Madagascar suggest that PEP with a double dose of rifampicin led to a similar reduction in incident leprosy, prompting the need for stronger PEP. The objective of this Phase 2 trial was to assess safety of a bedaquiline-enhanced PEP regimen (intervention arm, bedaquiline 800 mg with rifampicin 600 mg, BE-PEP), relative to the WHO recommended PEP with rifampicin 600 mg alone (control arm, SDR-PEP). From July 2022 to January 2023, consenting participants were screened for eligibility, including a heart rate-corrected QT interval (QTc) <450 ms and liver enzyme tests (ALT/AST) below 3× the upper limit of normal (ULN), before they were individually randomized 1:1 in an open-label design. Recruitment was sequential, by age group. Pediatric dosages were weight adjusted. Follow-up was done at day 1 post-dose (including ECG) and day 14 (including ALT/AST), with repeat of ALT/AST on the last follow-up at day 30 in case of elevation on day 14. The primary outcome was non-inferiority of BE-PEP based on a <10 ms difference in QTc 24 h after treatment administration, both unadjusted and adjusted for baseline QTc. Of 408 screened participants, 313 were enrolled, starting with 187 adults, then 38 children aged 13 to 17 years, and finally 88 children aged 5 to 12 years, of whom 310 (99%) completed all visits. Across all ages, the mean QTc change on BE-PEP was from 393 ms to 396 ms, not significantly different from the change from 392 ms to 394 ms on SDR-PEP (difference between arms 1.8 ms, 95% CI -1.8, 5.3, p = 0.41). No individual's QTc increased by >50 ms or exceeded 450 ms after PEP administration. Per protocol, all children were analyzed together, with no significant difference in mean QTc increase for BE-PEP compared to SDR-PEP, although non-inferiority of BE-PEP in children was not demonstrated in unadjusted analysis, as the upper limit of the 95% CI of 10.4 ms exceeded the predefined margin of 10 ms. Adjusting for baseline QTc, the regression coefficient and 95% CI (3.3; -1.4, 8.0) met the 10 ms non-inferiority margin. No significant differences in ALT or AST levels were noted between the intervention and control arms, although a limitation of the study was false elevation of ALT/AST during adult recruitment due to a technical error. In both study arms, one serious adverse event was reported, both considered unlikely related to the study drugs. Dizziness, nausea, headache, and diarrhea among adults, and headaches in children, were nonsignificantly more frequently observed in the BE-PEP group. In this study, we observed that safety of single-dose bedaquiline 800 mg in combination with rifampicin is comparable to rifampicin alone, although non-inferiority of QTc changes was demonstrated in children only after adjusting for the baseline QTc measurements. A Phase 3 cluster randomized efficacy trial is currently ongoing in the Comoros. ClinicalTrials.gov NCT05406479.